Anti-reflective hard coat film

JP7645144B2Active Publication Date: 2025-03-13AICA KOGYO CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021118388
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-19
Publication Date
2025-03-13
Estimated Expiration
2041-07-19

AI Technical Summary

Benefits of technology

【0011】 本発明のハードコートフィルムは、外部光源の反射が少なく視認性が良好であると共に、撥水·撥油性が高いため汚れが付きにくく、また汚れが付いた場合でも繰り返しの拭き取りや硬い綿布等での拭き取りに対して傷が付きにくい耐摩耗性に優れているため、画像表示装置用の反射防止フィルムとして有用である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645144000001
    Figure 0007645144000001
  • Figure 0007645144000002
    Figure 0007645144000002
  • Figure 0007645144000003
    Figure 0007645144000003
Patent Text Reader

Abstract

To provide an antireflection hard coat film having excellent wear resistance in which the reflection of an external light source is reduced to make visibility satisfactory, further, stains are less likely to be stuck owing to its high water-oil repellency, and scratches are hard to occur against repeated wiping or wiping with a hard cotton cloth or the like even when stains are stuck.SOLUTION: In an antireflection hard coat film, a hard coat film and a low refractive index layer are laminated on a base material film having light permeability in this order. The low refractive index layer comprises: a binder resin; hollow silica particles having the average particle diameter of 5 to 100 nm; alumina particles having the average particle diameter of 1 to 100 nm; and a surface conditioner, and the binder resin comprises ethylene oxide modified (meth)acrylate derived from pentaerythritol or trimethylol propane.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anti-reflective hard-coated film which has low reflection of an external light source, good visibility, and excellent antifouling and abrasion resistance. [Background technology]

[0002] Anti-reflective hard coat films are widely used in image display devices such as liquid crystal displays and organic electroluminescence displays because of their excellent visibility and low reflection of external light sources such as fluorescent lights. In particular, when touching an image display surface such as a touch panel with a finger, there is a problem that visibility is reduced due to adhesion of oil and dirt, so that a low reflectance of external light sources and anti-fouling properties are required, and in the case of devices that use a touch pen for input, higher abrasion resistance and scratch resistance are required.

[0003] A well-known anti-reflective hard-coated film has a hard-coat layer on the surface of a film substrate, and an anti-reflective layer with a low refractive index on top of it, but for example, a composition containing an ethylenically unsaturated group-containing fluoropolymer, a silicone compound having a siloxane skeleton, and a (meth)acrylate compound has been proposed as an anti-soiling anti-reflective film with excellent wiping properties (Patent Document 1). However, this anti-reflective film was not sufficient in terms of resistance to scratches even when repeatedly wiped or wiped with a hard cotton cloth.

[0004] On the other hand, as a resin composition with excellent abrasion resistance and low reflectance, a composition containing a silicone-grafted acrylic polymer, a compound having a methacryloyl group, and hollow colloidal silica has been proposed (Patent Document 2). However, although the cured film using this composition has excellent abrasion resistance, it cannot be said that it is sufficient in terms of antifouling. Therefore, there is room for improvement in order to make an antireflection film that has low reflection of external light sources, excellent visibility, and good abrasion resistance and antifouling properties. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication 2008-19402 [Patent Document 2] Patent Publication No. 2006-306950 Summary of the Invention [Problem to be solved by the invention]

[0006] The object of the present invention is to provide an anti-reflective hard-coated film which has excellent visibility with little reflection of external light sources, is highly water- and oil-repellent so that it is difficult to get dirty, and even if it does get dirty, it is difficult to scratch even when wiped repeatedly or with a hard cotton cloth, etc., and has excellent abrasion resistance. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention provides a hard coat layer and a low refractive index layer laminated in this order on a light-transmitting substrate film, the low refractive index layer containing a binder resin (A), hollow silica fine particles (B) having an average primary particle diameter of 5 to 100 nm, alumina fine particles (C) having an average primary particle diameter of 1 to 100 nm, and a surface conditioner (D), wherein (A) is Pentaerythritol tetraacrylate or trimethylolpropane triacrylate The present invention provides an anti-reflective hard coat film, which is characterized by containing an ethylene oxide-modified (meth)acrylate (a1) of the formula:

[0008] The invention of claim 2 provides an anti-reflective hard coat film characterized in that the blending ratio of (a1) in (A) is 50% by weight or more, and the invention of claim 3 provides an anti-reflective hard coat film characterized in that the blending amount of (C) is 2.0 to 15.0% by weight based on the total amount of solids in the low refractive index layer.

[0009] The invention of claim 4 provides the anti-reflection hard coat film according to any one of claims 1 to 3, characterized in that (D) is a fluorine-based silicone compound having a reactive functional group.

[0010] The invention of claim 5 provides the anti-reflective hard-coated film according to any one of claims 1 to 4, characterized in that the hard-coat layer has electrical conductivity. Effect of the Invention

[0011] The hard coat film of the present invention has good visibility with little reflection of external light sources, and is highly water- and oil-repellent, so it is less susceptible to dirt. Even if it does get dirty, it has excellent abrasion resistance and is less susceptible to scratches when wiped repeatedly or with a hard cotton cloth, etc., making it useful as an anti-reflection film for image display devices. BEST MODE FOR CARRYING OUT THEINVENTION

[0012] The anti-reflective hard coat film of the present invention is produced using two types of resin compositions: a hard coat (hereinafter referred to as HC) resin composition for forming a HC layer, and a low refractive index resin composition for forming a low refractive index layer. The low refractive index resin composition is a composition containing a binder resin (A), hollow silica fine particles (B), alumina fine particles (C), and a surface conditioner (D). In this specification, (meth)acrylate includes both acrylate and methacrylate.

[0013] The binder resin (A) used in the present invention is a main resin that disperses the above-mentioned (B) and (C) to form a low refractive index layer, and contains at least ethylene oxide (hereinafter referred to as EO) modified (meth)acrylate (a1) derived from pentaerythritol or trimethylolpropane. (a1) has the characteristic of being able to improve curability even in the case of a thin film, since it contains an EO chain and regenerates active radicals from peroxy radicals that have lost their polymerization activity due to oxygen inhibition.

[0014] Examples of the (a1) include EO-modified pentaerythritol tri(meth)acrylate, EO-modified pentaerythritol tetra(meth)acrylate, EO-modified dipentaerythritol tetra(meth)acrylate, EO-modified dipentaerythritol penta(meth)acrylate, EO-modified dipentaerythritol hexa(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, and EO-modified ditrimethylolpropane tetra(meth)acrylate, and can be used alone or in combination of two or more. Among these, 4- or more functional ones are preferred from the viewpoint of high reactivity, and EO-modified pentaerythritol tetraacrylate represented by the following formula (1) is particularly preferred. The number of polymerizations (n) of the EO modification is preferably 3 to 10, more preferably 4 to 8, and particularly preferably 4 to 5. [ka] (1) (n=a+b+c+d≒5 in Equation (1))

[0015] As the (A), a binder other than (a1) may be used. Examples of the binder (A) used other than (a1) include, for example, urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, polycarbonate (meth)acrylate, acrylic (meth)acrylate, and diene (meth)acrylate that are not EO-modified, as oligomers, and examples of the low molecular weight binder include (meth)acrylates having an aliphatic, alicyclic, polyether skeleton, or functional group such as a hydroxyl group or an amino group.

[0016] The ratio of (a1) in (A) is preferably 50% by weight or more, more preferably 60% by weight or more, and particularly preferably 90% by weight or more. By making it 50% by weight or more, the effect of reducing polymerization inhibition due to oxygen can be expected even in a thin film.

[0017] The amount of (A) is preferably 10 to 40% by weight, more preferably 12 to 35% by weight, and particularly preferably 15 to 30% by weight, based on the total solid content of the resin composition. By making it 10% by weight or more, sufficient film curing properties can be ensured, and by making it 40% by weight or less, the refractive index can be sufficiently reduced, thereby lowering the reflectance.

[0018] The hollow silica particles (B) used in the present invention are blended for the purpose of lowering the refractive index of the low refractive index layer. (B) is a silica particle having a cavity containing air with a refractive index of 1 inside, which has a function of lowering the refractive index of the low refractive index layer while maintaining the coating strength of the layer. While the refractive index of solid silica particles is about 1.45, the refractive index of (B) decreases as the occupancy rate of the internal cavities increases, and is about 1.15 to 1.40.

[0019] The primary average particle size of (B) is 5 to 100 nm, preferably 20 to 80 nm, and more preferably 40 to 70 nm. By setting it in this range, good dispersibility can be obtained without impairing the transparency of the low refractive index layer. In particular, if it is 40 to 70 nm, the occupancy rate of the cavity can be increased to lower the refractive index while ensuring a shell thickness that does not cause insufficient strength. The average particle size is the median diameter (d=50) measured by a laser diffraction / scattering method in accordance with JISZ8825-1.

[0020] The blending amount of the (B) is preferably 40 to 70% by weight, more preferably 45 to 65% by weight, based on the total solid content of the resin composition. By making it 40% by weight or more, the refractive index can be sufficiently lowered, and by making it 70% by weight or less, sufficient abrasion resistance can be ensured. An example of a commercially available product is Sururia 4320 (product name: manufactured by JGC Catalysts and Chemicals, solid content 20.5%, average primary particle size 60 nm).

[0021] The alumina fine particles (C) used in the present invention are blended for the purpose of increasing the hardness of the low refractive index layer and improving the abrasion resistance. The primary average particle size of (C) is 1 to 100 nm, preferably 5 to 50 nm, and more preferably 10 to 30 nm. By making it 1 nm or more, it is possible to expect improvement in abrasion resistance, and by making it 100 nm or less, it is possible to ensure sufficient total light transmittance without increasing haze.

[0022] The amount of (C) is preferably 2.0 to 15.0% by weight, more preferably 3.0 to 12.0% by weight, and particularly preferably 4.0 to 10.0% by weight, based on the total solid content of the resin composition. By making it 3.0% by weight or more, sufficient abrasion resistance can be ensured, and by making it 15.0% by weight or less, the reflectance can be kept sufficiently low. An example of a commercially available product is ALMIBK-M47 (product name: manufactured by CIK Nanotech Co., Ltd., solid content 15%, average particle size 20 nm).

[0023] The surface conditioner (D) used in the present invention is blended for the purpose of improving the slip property of the low refractive index layer to improve the abrasion resistance, and also improving the water repellency and antifouling properties by increasing the water repellency. Examples include silicone-based, fluorine-based, and acrylic-based compounds, and it is preferable that the compound has a reactive functional group capable of forming a cured coating film by polymerization with a binder resin, since the effect can be maintained for a long time without being lost over time due to bleeding or the like from the cured film. In particular, fluorine-based silicone compounds are preferable because they are easy to segregate on the coating film surface after coating and drying due to their low surface free energy, and abrasion resistance and antifouling properties can be stabilized for a long time.

[0024] The amount of (D) is preferably 1 to 25% by weight, more preferably 3 to 15% by weight, and particularly preferably 5 to 12% by weight, based on the total solid content of the resin composition. By making it 1% by weight or more, it is expected that the abrasion resistance and antifouling properties can be improved, and by making it 25% by weight or less, sufficient curing properties can be ensured. An example of a commercially available product is X-71-1203M (trade name: manufactured by Shin-Etsu Chemical Co., Ltd., solid content 20%, fluorine-based silicone compound having a reactive functional group).

[0025] The HC resin composition for forming the HC layer located below the low refractive index layer of the present invention preferably contains a polyfunctional urethane (meth)acrylate (hereinafter referred to as polyfunctional ureac) as a binder.

[0026] The polyfunctional ureac preferably contained in the HC resin composition has excellent scratch resistance due to the cohesive force of hydrogen bonds derived from urethane bonds. For example, it can be obtained by reacting polyisocyanate with (meth)acrylate having a hydroxyl group. Examples of polyisocyanates that can be used include hexamethylene diisocyanate (hereinafter referred to as HDI), isophorone diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, hydrogenated xylylene diisocyanate, methylcyclohexylene diisocyanate, HDI isocyanurate, and IPDI isocyanurate, and these may be used alone or in combination of two or more. Among these, aliphatic and alicyclic diisocyanates that have high weather resistance and are not easily yellowed are preferred, and among them, HDI, which has high stretchability, is particularly preferred.

[0027] The (meth)acrylate having a hydroxyl group used in the polyfunctional urea is, for example, trimethylolpropane di(meth)acrylate, glycerin di(meth)acrylate, pentaerythritol di(meth)acrylate, diglycerin di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, dipentaerythritol di(meth)acrylate, etc., which are bifunctional, and diglycerin tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, which are trifunctional and highly curable. Among these, pentaerythritol triacrylate (hereinafter referred to as PETA) is preferred.

[0028] Furthermore, by making the HC layer conductive, it is possible to impart antistatic properties to the antireflection film. To make the HC layer conductive, for example, a conductive polymer such as a π-conjugated polymer, an antistatic agent such as a compound containing a quaternary ammonium salt, or a conductive metal oxide such as indium tin oxide or antimony-doped tin oxide can be added to the HC resin. Among these, it is preferable to use a π-conjugated conductive polymer in terms of excellent transparency and dispersibility.

[0029] The π-conjugated conductive polymer can be any known organic polymer whose main chain is composed of a π-conjugated system. For example, polythiophene-based, polypyrrole-based, polyaniline-based, polyphenylene-based, polyacetylene-based, polyphenylenevinylene-based, polyacene-based, polythiophenevinylene-based, and copolymers thereof can be mentioned. Among these, polythiophene-based compounds are preferred in terms of stability and easy availability.

[0030] The polythiophene compound is a polymer of thiophene, a sulfur-containing heterocyclic compound, and becomes conductive when electrons are added to or removed from the conjugated n orbital by doping. In particular, poly(3,4-ethylenedioxythiophene) (hereinafter PEDOT) is preferred because it has improved conductivity when combined with poly(4-styrenesulfonate) (hereinafter PSS), has high environmental stability, and has high light transmittance in thin films.

[0031] The content of the polythiophene compound in the HC resin is preferably 0.3 to 5.0% by weight, more preferably 0.5 to 3.0% by weight, and particularly preferably 0.8 to 2.0% by weight, based on the total solid content. By making it 0.3% by weight or more, sufficient electrical conductivity can be imparted, and by making it 5.0% by weight or less, the appearance of the HC layer can be maintained good.

[0032] It is preferable to blend a photopolymerization initiator in the HC resin composition and the low refractive index resin composition of the present invention in order to improve the curability by ultraviolet irradiation. The photopolymerization initiator generates radicals when irradiated with ultraviolet rays or electron beams, and the radicals trigger a polymerization reaction. General-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, benzyl ketals include 2,2-dimethoxy-1,2-diphenylethan-1-one, α-hydroxyacetophenones include 1-hydroxy-cyclohexyl-phenyl-ketone and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, α-aminoacetophenones include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, and acylphosphine oxides include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, which may be used alone or in combination of two or more.

[0033] In the case of the HC resin composition, the photopolymerization initiator preferably contains an α-hydroxyacetophenone type which is less prone to yellowing, and examples of commercially available products include Omnirad127, Omnirad184, and Omnirad2959 (product name: manufactured by IGM Resins). Among these, Omnirad2959, which is particularly less prone to yellowing and has excellent scratch resistance, is preferred. The amount of the photopolymerization initiator to be blended with respect to 100 parts by weight of the radical polymerizable component in the HC resin composition is preferably 1 to 15 parts by weight, more preferably 2 to 10 parts by weight.

[0034] In the case of a low refractive index resin composition, the photopolymerization initiator preferably contains an α-hydroxyacetophenone system as in the case of the HC resin composition, and Omnirad127 (2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one) is particularly preferred because it is less susceptible to polymerization inhibition by oxygen. The amount of the photopolymerization initiator blended per 100 parts by weight of the radical polymerizable component in the low refractive index resin composition is preferably 1 to 10 parts by weight, more preferably 2 to 8 parts by weight.

[0035] To the composition of the present invention, reactive diluents, ultraviolet absorbers, antioxidants, adhesion promoters, bluing agents, defoamers, thickeners, suspending agents, antistatic agents, antifogging agents, antibacterial agents, organic fine particles, and the like may be added as necessary within the range not impairing the performance.

[0036] When applying the HC resin composition and the low refractive index resin composition, they may be diluted with a solvent to improve the coating properties. Examples of dilution solvents include alcohol-based solvents such as ethanol, n-propyl alcohol, isopropyl alcohol (hereinafter IPA), n-butyl alcohol, isobutyl alcohol, and diacetone alcohol, ketone-based solvents such as acetone, methyl ethyl ketone (hereinafter MEK), methyl isobutyl ketone, and cyclohexanone, ester-based solvents such as ethyl acetate and butyl acetate, and ether-based solvents such as PGM, diethyl ether, and diisopropyl ether, and these can be used alone or in combination of two or more. The solid content when diluted is 1 to 70%, but is not particularly specified and can be appropriately set to a viscosity that is easy to apply.

[0037] Examples of the substrate film to which the HC resin composition is applied include polyester film, triacetyl cellulose film, polycarbonate film, polysulfone film, nylon film, cycloolefin film, acrylic film, polyimide film, ABS film, polyolefin film, PVC film, PVA film, etc. Among them, a biaxially stretched polyester film is preferably used from the viewpoints of weather resistance, processability, dimensional stability, etc. The thickness of the film may be about 25 μm to 500 μm.

[0038] For the purpose of improving adhesion to the HC resin composition, the substrate film may be subjected to a surface treatment such as a primer treatment, a sandblasting method, a solvent treatment, or the like to make the surface uneven, or a surface oxidation treatment such as a corona discharge treatment, a chromic acid treatment, or an ozone / ultraviolet light irradiation treatment.

[0039] The method for applying the HC resin composition and the low refractive index resin composition is not particularly limited, and the composition can be formed by a known coating method such as spray coating, roll coating, die coating, air knife coating, blade coating, spin coating, reverse coating, gravure coating, or wire bar coating, or a printing method such as gravure printing, screen printing, offset printing, or inkjet printing.

[0040] The thickness of the HC resin composition when dry can be 1 μm to 10 μm, but is not limited thereto. The thickness of the low refractive index resin composition applied onto the hard coat resin layer when dry is preferably 50 to 200 nm, more preferably 80 to 150 nm. If the thickness of the low refractive index layer is within this range, it is possible to sufficiently reduce the reflectance.

[0041] Examples of light sources for ultraviolet irradiation used when curing the HC resin composition and the low refractive index resin composition include low pressure mercury lamps, high pressure mercury lamps, extra high pressure mercury lamps, carbon arc lamps, xenon lamps, metal halide lamps, LED lamps, and electrodeless ultraviolet lamps, and the atmosphere for irradiation may be air or an inert gas such as nitrogen or argon. In addition, the curability can be further improved by heating the coating film during ultraviolet irradiation using a back roll or an IR heater. Irradiation conditions include an irradiation intensity of 500 mW / cm. 2 ~3000mW / cm 2 , exposure dose 50-400mJ / cm 2 The ultraviolet irradiation is carried out after the film is molded, but is not limited to this. 2 ) may also be used for semi-cure.

[0042] When the HC resin layer is made conductive, the surface resistivity of the anti-reflection film is 1×10 12 Ω / □ or less is preferable, 1×10 10 More preferably, it is 1×10 12 By setting the resistance to Ω / □ or less, sufficient antistatic performance can be ensured.

[0043] The present invention will be described in detail below with reference to examples and comparative examples, but these are illustrative and are not intended to be limiting. Unless otherwise specified, measurements were taken at room temperature of 25°C and at a relative humidity of 65%. The amounts of the ingredients are in parts by weight.

[0044] HC resin composition A hexafunctional ureac A obtained by reacting HDI and PETA was used as the binder, and Omnirad2959 (product name: manufactured by IGM Resins) was used as the photopolymerization initiator in the proportions shown in Table 1. The mixture was diluted with ethyl acetate and PGM to a solid content of 40%, and stirred until uniformly dissolved and dispersed to obtain an HC resin composition. In addition, Z-885-10ASL-2 (product name: manufactured by Aica Kogyo Co., Ltd., solid content 30%) was used as the conductive HC agent, which is a urethane acrylate of the same composition mixed with PEDOT / PSS at 1% of the total solid content.

[0045] Low refractive index resin composition As the (A), Miramer M4004 (trade name: manufactured by Miwon, tetrafunctional EO-modified pentaerythritol tetraacrylate, n≒5) and Miramer M3130 (trade name: manufactured by Miwon, trifunctional EO-modified trimethylolpropane triacrylate, n≒3) were used; as the (B), Sururia 4320 (trade name: manufactured by JGC Catalysts and Chemicals, solid content 20.5%, primary average particle size 60 nm, refractive index 1.3) was used; as the (C), M47 (trade name: manufactured by CIK Nanotech, solid content 15%, average particle size 20 nm, MIBK dilution) was used; as the (D), X-71-1203M (trade name: manufactured by Shin-Etsu Chemical Co., Ltd., solid content 20%, reactive functional group-containing fluorine-based silicone compound) was used; as the (D), Omnirad 127 (trade name: IGM A low refractive index resin composition was obtained by using a mixture of M460 (manufactured by Nippon Kayaku Co., Ltd., EO-modified diglycerin tetraacrylate) and DPHA (manufactured by Nippon Kayaku Co., Ltd., dipentaerythritol hexaacrylate) as binders in the proportions shown in Table 1, diluting the mixture with IPA and PGM (IPA:PGM=1:1) to a solid content of 3%, and stirring until the mixture was uniformly dissolved and dispersed to obtain a low refractive index resin composition.

[0046] Table 1 JPEG0007645144000002.jpg70135

[0047] The evaluation method was as follows.

[0048] Preparation of HC layer The HC resin composition was applied to a PET film U403 (product name: manufactured by Toray Industries, Inc., thickness 100 μm, with easy-adhesion layer) to a dry thickness of 3 μm, and dried at 80° C. for 1 minute. Then, using an ultraviolet exposure device ECS-151U manufactured by iGraphics Co., Ltd., the coating was exposed to 100 mW / cm 2 ,800mJ / cm 2 The mixture was cured under the above conditions to prepare an HC film.

[0049] Creating anti-reflective film A low refractive index resin composition was applied onto the hard coat layer prepared above so that the dry film thickness was 100 nm, and dried at 80° C. for 1 minute. Thereafter, the composition was exposed to a UV light of 100 mW / cm using an ECS-151U UV exposure device manufactured by iGraphics Co., Ltd. 2 ,800mJ / cm 2 , and cured under nitrogen atmosphere to form an anti-reflective film.

[0050] Coating haze: The anti-reflection film was measured in accordance with JIS K7361-1 using Haze-GARD2 manufactured by Toyo Seiki Seisakusho Co., Ltd., with 1.0% or less being rated as ◯ and over 1.0% being rated as x.

[0051] Minimum reflectance: Using the above anti-reflection film, the side opposite the coated side was scratched with sandpaper, painted over with a black pigment marker, and then black PET was attached to set the reflectance of the opposite side to 0%.Then, the reflectance of the HC side was plotted in 1 nm increments in the range of 300 nm to 780 nm using a spectrophotometer to measure the minimum reflectance, with 1.5% or less marked as ◯ and over 1.5% marked as ×.

[0052] Abrasion resistance: A load of 200 g / cm2 was placed on steel wool #0000 and reciprocated 10 times. When visually observed, no scratches were observed, rated as ○, slight scratches as △, and numerous scratches as ×.

[0053] Water contact angle: In accordance with the sessile drop method of JIS R 3257:1999, using a DMs-400 manufactured by Kyowa Interface Science Co., Ltd., water was dropped onto a normal sample at room temperature and the contact angle was measured after leaving it to stand for 30 seconds. A contact angle of 115° or more was evaluated as ◎, a contact angle of 105° or more but less than 115° was evaluated as ○, and a contact angle of less than 105° was evaluated as ×.

[0054] Surface resistivity: Measured using a high resistance resistivity meter Hiresta UXMCP-HT800 manufactured by Mitsubishi Chemical Analytical Corp. at an applied voltage of 100 V and a measurement time of 1 minute. Note that the surface resistivity was measured only in Examples 3 and 5.

[0055] Evaluation results Table 2 JPEG0007645144000003.jpg65135

[0056] The examples were good with no problems in terms of haze, minimum reflectance, abrasion resistance, and water contact angle. In addition, the example 5 in which the HC layer was made conductive had a surface resistivity of 1×10 12 Ω / □ or less, ensuring sufficient antistatic performance.

[0057] On the other hand, Comparative Example 1, which did not contain (C), had poor abrasion resistance and a low water contact angle, and Comparative Example 2, which did not contain (B), had a high minimum reflectance and a low water contact angle. Comparative Examples 3 and 4, which did not contain (a1), also had poor abrasion resistance, and neither was suitable for the present invention.

Claims

1. An anti-reflective hard coat film comprising a hard coat layer and a low refractive index layer laminated in this order on a light-transmitting substrate film, the low refractive index layer comprising a binder resin (A), hollow silica fine particles (B) having an average primary particle diameter of 5 to 100 nm, alumina fine particles (C) having an average primary particle diameter of 1 to 100 nm, and a surface conditioner (D), the (A) comprising an ethylene oxide-modified (meth)acrylate of pentaerythritol tetraacrylate or trimethylolpropane triacrylate (a1).

2. 2. The anti-reflective hard coat film according to claim 1, wherein the blending ratio of (a1) in (A) is 50% by weight or more.

3. 3. The anti-reflection hard coat film according to claim 1, wherein the blending amount of said (C) is 2.0 to 15.0% by weight based on the total amount of solids in the low refractive index layer.

4. 4. The anti-reflective hard coat film according to claim 1, wherein the component (D) is a fluorine-based silicone compound having a reactive functional group.

5. 5. The anti-reflective hard-coated film according to claim 1, wherein the hard-coat layer has electrical conductivity.

Citation Information

Patent Citations

  • Photosensitive resin composition and film having cured coating thereof

    JP2006306950A

  • Curable resin composition and antireflection film

    JP2008019402A

  • Anti-reflection film and electronic image display device using the same

    JP2009025568A

  • Optical laminate, manufacturing method of optical laminate, polarizing plate, and image display device

    JP2009069429A

  • Inkjet ink, ink set, and printing method

    JP2020023620A